Reliability and sensitivity of a simple isometric posterior lower limb muscle test in professional football players - McCall, A.; Nedelec, M.; Carling, C.; Le Gall, F.; Berthoin, S.; Dupont, G. (Journal of Sports Sciences, 2015)
This study aimed (1) to determine the reliability of a simple and quick test to assess isometric posterior lower limb muscle force in professional football players and (2) verify its sensitivity to detect reductions in force following a competitive match. Twenty-nine professional football players performed a 3-s maximal isometric contraction of the posterior lower limb muscles for both legs with players lying supine. Both legs were tested using a knee angle of 90° and 30° measured on a force plate. Players were tested twice with one week between sessions to verify reliability. Sensitivity was tested following a full competitive football match. The test showed high reliability for dominant leg at 90° (CV = 4.3%, ICC = 0.95, ES = 0.15), non-dominant leg at 90° (CV = 5.4%, ICC = 0.95, ES = 0.14), and non-dominant leg at 30° (CV = 4.8%, ICC = 0.93, ES = 0.30) and good reliability for dominant leg at 30° (CV = 6.3%, ICC = 0.86, ES = 0.05). The measure was sensitive enough to detect reductions in force for dominant leg at 90° (P = 0.0006, ES > 1), non-dominant leg at 90° (P = 0.0142, ES = 1), and non-dominant leg at 30° (P = 0.0064, ES > 1) and for dominant leg at 30° (P = 0.0016, ES > 1). In conclusion, the present test represents a useful and practical field tool to determine the magnitude of match-induced fatigue of the posterior lower limb muscles and potentially to track their recovery.